Functional Electrochemistry: On-Nerve Assessment of Electrode Materials for Electrochemistry and Functional Neurostimulation - Jason A. Miranda; Adrien Rapeaux; Isabelle C. Samper; Carolina Silveira; David R. Wille; Gerald E. Hunsberger; Wesley J. Dopson; Huanfen Yao; Annapurna Karicherla; Daniel J. Chew (IEEE Open Journal of Engineering in Medicine and Biology, 2024)
Emerging therapies in bioelectronic medicine highlight the need for deeper understanding of electrode material performance in the context of tissue stimulation. Electrochemical properties are characterized on the benchtop, facilitating standardization across experiments. On-nerve electrochemistry differs from benchtop characterization and the relationship between electrochemical performance and nerve activation thresholds are not commonly established. This relationship is important in understanding differences between electrical stimulation requirements and electrode performance. We report functional electrochemistry as a follow-up to benchtop testing, describing a novel experimental approach for evaluating on-nerve electrochemical performance in the context of nerve activation. An ex-vivo rat sciatic nerve preparation was developed to quantify activation thresholds of fiber subtypes and electrode material charge injection limits for platinum iridium, iridium oxide, titanium nitride and PEDOT. Finally, we address experimental complexities arising in these studies, and demonstrate statistical solutions that support rigorous material performance comparisons for decision making in neural interface development.